Spontaneous Obliteration of Pial Arteriovenous Malformations: A Review of 27 Cases - Patel, Maneesh C.; Hodgson, Timothy J.; Kemeny, Andras A.; Forster, David M. (American Journal of Neuroradiology, 2001)
BACKGROUND AND PURPOSE: Brain arteriovenous malformations (AVMs) occur in approximately 0.14% of the population. The most common presentations are hemorrhage (50%) and seizures (25%). Although they are congenital abnormalities, their angioarchitecture may vary over time. A rare but well-recognized phenomenon of AVMs is that of spontaneous obliteration. It is not known what factors predispose to spontaneous obliteration. The purpose of our study was to determine whether spontaneous thrombosis of AVMs can be predicted by their angioarchitecture and whether there is any risk of recurrence once obliteration has occurred.METHODS: We retrospectively reviewed the angiographic and cross-sectional imaging data amassed over an 18-year period, including follow-up imaging studies and mail surveys of referring and family physicians. A control group was obtained from contemporaneous AVMs of a similar size.RESULTS: We identified 28 cases of spontaneous obliteration in a series of 2162 patients. The mean time between initial diagnostic angiography and angiographic obliteration was 10 months, during which time there was no intervention and no history of repeat hemorrhage; nor had hemorrhage recurred during the follow-up period (mean, 53 months). Most of the AVMs were deep (22/27) with only one draining vein (21/27) and few feeding arteries. In more than half the cases (15/27) drainage was exclusively into the superficial venous system.CONCLUSION: Spontaneous obliteration is rare (1.3%). Common features include hemorrhagic presentation and few arterial feeding vessels. Although we found no instance of repeat hemorrhage during the follow-up period, AVMs can recanalize, and follow-up is therefore recommended.